Psychosocial aspects of childhood cancer survivors - Jong Jin Seo (Korean Pediatric Society, 2010)
The majority of childhood cancer survivors and their families will be psychologically healthy, but may desire and benefit from preventive care. A significant portion of the survivor population will be psychosocially distressed in various aspects by their harsh experience of long cancer treatment, and may warrant professional intervention and treatment. Pediatricians should be aware of the late psychological effects that can occur a year or 2 after treatment, possibly in many aspects of a survivor's life. Not only the cancer diagnosis, but also treatments such as chemotherapy, irradiation, and surgical intervention may exert different long-term effects on the psychosocial outcomes of survivors. Pediatricians need to be more concerned with maintaining and improving the psychological health of this growing number of childhood cancer survivors through long-term follow-up clinics, community support, or self-help groups. Research on all of the psychosocial aspects of childhood cancer survivors is important to recognize the reality and problems they face in Korea.